Epidemiological survey of DMFT and Xerostomia in Brazilian university students: relationships with oral health (Research, Society and Development, 2023)
The DMFT is the sum of decayed (D), missing (M) and indices of filled teeth (F). Xerostomia is the most prevalent form of oral dryness. This article aims to describe the DMF and xerostomia indexes of Brazilian Dentistry students. field, with cross-sectional and direct observation of the extensive type using a questionnaire and non-probabilistic sampling. For data collection, the chain dissemination procedure entitled snowball was used. Data referring to xerostomia were also investigated, and were obtained through a questionnaire, which consisted of 4 questions. The data obtained were analyzed using the Statistical Package for Social Science (SPSS 21). No significant differences were found between participants.